Effects of multicomponent exercise on frailty status and physical function in frail older adults: A meta-analysis and systematic review - Xinyu Yang; Shasha Li; Lingfen Xu; Haibing Liu; Yue Li; Xiaofang Song; Jianyi Bao; Shufang Liao; Yingxue Xi; Guojing Guo (Experimental Gerontology)
Objectives: The study aimed to carry out a systematic review and meta-analysis to explore the effects of multicomponent exercise on frailty status and physical function in frail older adults. Design: A systematic review and meta-analysis. Setting and participants: Older adults aged ≥60 years diagnosed with frailty using the Frailty Assessment Tool. Methods: PubMed, EMBASE, Web of Science, Cochrane Library, CNKI, and Wanfang were searched from inception to March 10, 2024. Two reviewers independently screened and selected the publications, extracted the data, and assessed risk of bias. This study included randomized controlled trials and quasi-experimental designs. Review Manager 5.4 was used for data analysis. Results: Twenty-eight randomized controlled trials with 4857 older adults were included. Multicomponent exercise significantly improved frailty status (SMD = −1.40, 95 % CI:−2.05 to −0.75, P < .05) and had a significant impact on physical function (muscle strength: SMD = 0.31, 95 % CI: 0.01–0.61, P < .05; gait speed: SMD = 0.27, 95 % CI: 0.02–0.52, P < .001; balance: SMD = 0.27, 95 % CI: 0.05–0.49, P = .02; Short Physical Performance Battery [SPPB]: SMD = 1.03, 95 % CI: 0.65–1.42, P < .001; and Timed Up and Go [TUG]: SMD = −3.05, 95 % CI: −3.90 to −2.19, P < .001). Subgroup analysis suggested that a 12-week duration is optimal for multicomponent exercise interventions, demonstrating significantly greater effectiveness in hospital compared with out-of-hospital. Conclusions: Multicomponent exercise intervention can improve frailty status in older adults and promote enhancement of physical functional abilities (muscle strength, gait speed, balance, SPPB, and TUG). Therefore, a possible protective effect of multicomponent exercise in frailty older adults is suggested.